2023
DOI: 10.3390/ijms24119399
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Cyanidin-3-Glucoside on Inflammatory Bowel Diseases: Investigating New Mechanisms for Emerging Interventions

Maximos Frountzas,
Eva Karanikki,
Orsalia Toutouza
et al.

Abstract: Cyanidin-3-O-glucoside (C3G), the most widely distributed anthocyanin (ACN) in edible fruits, has been proposed for several bioactivities, including anti-inflammatory, neuro-protective, antimicrobial, anti-viral, anti-thrombotic and epigenetic actions. However, habitual intake of ACNs and C3G may vary widely among populations, regions, and seasons, among individuals with different education and financial status. The main point of C3G absorption occurs in the small and large bowel. Therefore, it has been suppos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 183 publications
0
2
0
Order By: Relevance
“…Cyanidin-3-glucoside inhibits the NF-κB pathway. Also, it was reported to inhibit the interferon-mediating inflammatory cascades and reduce the proinflammatory cytokines, such as interferon-γ, TNF-α, interleukin (IL)-5, IL-9, and IL-10 [95,98].…”
Section: Discussionmentioning
confidence: 99%
“…Cyanidin-3-glucoside inhibits the NF-κB pathway. Also, it was reported to inhibit the interferon-mediating inflammatory cascades and reduce the proinflammatory cytokines, such as interferon-γ, TNF-α, interleukin (IL)-5, IL-9, and IL-10 [95,98].…”
Section: Discussionmentioning
confidence: 99%
“…Anthocyanins are a common class of water-soluble pigments that are characterized by their antioxidant, 23 anti-inflammatory, 24 neuroprotective, 25 and anti-diabetic properties. 26 With regard to the effects on the cardiovascular system, Liu et al demonstrated that anthocyanin (C3G) protects against diabetes-related endothelial cell dysfunction by increasing adiponectin secretion.…”
Section: Discussionmentioning
confidence: 99%